Secondary organic aerosol formation from photooxidation of γ-butyro and γ-valero-lactone: A combined experimental and theoretical study. (1st May 2022) - Tajuelo, Mercedes; Rodriguez, Ana; Aranda, Alfonso; Díaz-de-Mera, Yolanda; Tucceri, María E.; Rodriguez, Diana
Abstract: The formation of secondary organic aerosol (SOA) generated by OH-photooxidation of γ-butyrolactone (GBL) and γ-valerolactone (GVL) in the presence of OH, NO, H2 O vapour and aerosol seeds ((NH4 )2 SO4 and CaCl2 ) has been investigated for the first time. Experiments were conducted in a smog chamber at 298 K and atmospheric pressure. Lactone's decay was followed by gas chromatography with a mass spectrometric detector (GC-MS), and the temporal evolution of the SOA was monitored using a fast mobility particle sizer (FMPS). The SOA yield increases slightly when the initial GVL concentration increases. On the other hand, SOA formation is minor for GBL, and it rises slightly at low concentrations. In the case of GVL, the organic aerosol formation can be tentatively expressed by a one-product gas/particle partitioning absorption model. The particle number concentration, mass and yield decrease in the presence of NO but increase at higher relative humidity (RH) and seed surface area within the studied range. Acetic acid and succinic anhydride for GVL, and succinic anhydride for GBL were experimentally identified as oxidation products both in gas and particle phase using thermal desorption followed by GC-MS. Moreover, the theoretical studies carried out to complement the experimental results indicate that H-abstraction at the carbon site adjacent to the heterocyclic oxygen is the predominant pathway, being even more favourable when H2 O was added. Also, under atmospheric conditions, the opening of the ring of the corresponding oxy-radicals and their subsequent fragmentation could be the possible explanation for the formation of detected products and the higher yield of SOA in the presence of H2 O and absence of NO. Considering these results, the formation of SOA from the use of both lactones as potential biofuels is few significative, although SOA generation may be enhancement by particle-phase heterogeneous reactions catalyzed by humidity and the acidity of seed aerosols present in real atmosphere. Graphical abstract: Image 1 Highlights: SOA yields were slightly higher for OH-photooxidation of GVL than GBL. Lower NOx levels and higher relative humidity enhance SOA formation. SOA mass and yield depend on surface area of (NH4 )2 SO4 and CaCl2 seed particles. Low SOA generation for both lactones favors their use as biofuels.